Serpentinisasi Pada Batuan Ultramafik dan Implikasinya Terhadap Eksplorasi Endapan Nikel Laterit - , Sufriadin ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
Serpentine is a group of magnesium hydro-silicate mineral (Mg3Si205(OH)4) that formed through hydration reaction of ultramafic rock with olivine and pyroxene as the main phases. Three serpentine minerals may be distinguished on the basis of their morphology as platy lizardite, fibrous chrysotile, and wary antigorite. Serpentine textures consist of pseudomorphic (mesh, hourglass, and bastite), and non - peudomorphic (interpenetrating and interlocking). Lizardite contains highest Fe and Mg is highest in chrysotile among the three serpentine minerals. In general, serpentinization process is accompanied by the formation of opaque minerals such as magnetite, awaruite, and pentlandite. Serpentinization degree of peridotite lead to rock become darker, finer grain texture, and higher magnetic susceptibility.